A Systematic Review of Business Intelligence Technology for Decision-Making - Yojan FELIX-CARHUANCHO; Jean FRANCIA-LAGUNAS; Javier GAMBOA-CRUZADO; Jorge MAYHUASCA-GUERRA; Juan PACHECO-TORRES; Alberto ALVA-ARÉVALO; Caleb RÍOS-VARGAS (Communications of International Proceedings, 2021)
Currently, the top management in companies presents important information with the help of slides. However, this method could lead to significant errors in decision-making as the necessary steps to preserve data reliability for decision-making may not have been taken. The objective of this research is to systematically review and analyze the articles in the literature that provide competitive advantage by using Business Intelligence (BI) tools. The articles for this research were sourced from ACM Digital Library, ERIC, IEEE Xplore, Microsoft Academic, ProQuest, Taylor & Francis Online and Wiley Online Library.  A total of 2,666,590 articles were extracted from these sources. After choosing certain selection criteria and formulating quality questions on the studies, only 96 articles from the total extracted articles were selected for the present research work. Consequently, most suitable BI tools for decision-making are proposed.
Keywords: Business intelligence; Decision-making; Data visualization; Business analytics; Data warehouse; Systematic review.